2011
DOI: 10.1128/aem.02766-10
|View full text |Cite
|
Sign up to set email alerts
|

Metallic Copper as an Antimicrobial Surface

Abstract: 3Bacteria, yeasts, and viruses are rapidly killed on metallic copper surfaces, and the term "contact killing" has been coined for this process. While the phenomenon was already known in ancient times, it is currently receiving renewed attention. This is due to the potential use of copper as an antibacterial material in health care settings. Contact killing was observed to take place at a rate of at least 7 to 8 logs per hour, and no live microorganisms were generally recovered from copper surfaces after prolon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

19
1,087
2
18

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 1,334 publications
(1,126 citation statements)
references
References 41 publications
19
1,087
2
18
Order By: Relevance
“…Sci., 17/2, 2016, 396-403 397 have overall benefits due to better fish growth induced by increased feeding rate, reduced fish stress and lower labor costs from net cleanings and changes (Yigit et al, 2013). The antimicrobial properties of copper alloys in health care applications are well documented (Grass et al, 2011). Recently, copper alloys have been fabricated into wire mesh materials for use in cage nets in place of polymer netting.…”
Section: Introductionmentioning
confidence: 99%
“…Sci., 17/2, 2016, 396-403 397 have overall benefits due to better fish growth induced by increased feeding rate, reduced fish stress and lower labor costs from net cleanings and changes (Yigit et al, 2013). The antimicrobial properties of copper alloys in health care applications are well documented (Grass et al, 2011). Recently, copper alloys have been fabricated into wire mesh materials for use in cage nets in place of polymer netting.…”
Section: Introductionmentioning
confidence: 99%
“…Initiatives to minimize bacterial colonization at the time of insertion have been studied in the past with slow permeation in the clinical setting [1,39,48]. Several preclinical and clinical studies support the use of copper alloy touch surfaces to reduce the burden of bacteria in healthcare settings [10,11,33], but few studies support the use of copper implants to reduce periprosthetic infections [6,18,27,41]. The ideal antibacterial coating should be biocompatible, thin, dense, and firm with precise decay of the active material.…”
Section: Discussionmentioning
confidence: 99%
“…The U.S. Environmental Protection Agency has approved over 300 copper alloys as antimicrobial touch surfaces [11] and its public health benefit has been supported by a multicenter study that showed patients treated in intensive care units with copper alloy surfaces had a significantly lower incidence of hospital-acquired infections and/or colonization with methicillin-resistant Staphylococcus aureus or vancomycin-resistant enterococci than did patients treated in standard rooms [33]. Regarding the use of implants containing copper, practically all clinical experience comes from the use of intrauterine contraceptive devices made of copper [21].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the development of innovative antibacterial surfaces presenting long-term effective operational lifetimes, biocompatibility and mechanical resistance is a timely research subject. Antibacterial Cu-colloids have been reported during the last 3 decades showing their antibacterial activity [1]. Bacteria, yeasts, and viruses have been abated on metallic copper surfaces, and the term "contact killing" has been coined for this process.…”
Section: Introductionmentioning
confidence: 99%